STRATEGI MANAJEMEN PERUBAHAN DALAM MENINGKATKAN KUALITAS MANAJERIAL PENDIDIKAN ISLAM DI MAN 1 PAMEKASAN - Atiqullah Atiqullah; Milda Karya Puspasari (Prodi MPI Fakultas Tarbiyah IAIN Madura, 2018)
The educational institution must have a strategy in bringing about an improvement or change. Where strategy is a way in the process toward the goal. The progress of educational institutions today is highly demanded because of the strong flow of competition among educational institutions. Ability to compete with other institutions is a succes of educational institutions or the ability to give trust to the communit. Succes in an educational institution depends on the management applied within an institution. As well as the role of managers in embracing management systems, educational organizations and education planning to become a conducive educational environment. Because if the managed management is so good then the result to be achieved in the education will run effectively and produce a succes. Thus institutionsshould be able to embrace change management strategies in improving the quality of managerial education of Islam well.